2005
DOI: 10.1088/0031-9120/40/3/001
|View full text |Cite
|
Sign up to set email alerts
|

Introducing relativity: less may be more

Abstract: This article shows how relativity can be introduced in four stages, each building on those before it, but the teacher can choose to stop after whichever stage he/she believes the pupils are capable of tackling. Choosing how far to goMany A-level students are eager to know something about relativity. They are excited by the strange ideas they have heard about: for example, time dilation and the mysterious equation E = mc 2 . But their initial interest is liable to evaporate quickly when faced with Lorentz trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…Based on the study data, in conclusion, it can be said that the participants found the subject of Special Relativity interesting. According to Ogborn (2005), although students find Special Relativity very interesting when they first hear about the concept of time dilation and the mysterious formula of E=mc 2 , the mathematical difficulties that they experience when they meet the Lorentz transformations cause them to lose interest. In the present study, the mathematical difficulties stand out as one of the problems that the participants faced when learning about relativity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study data, in conclusion, it can be said that the participants found the subject of Special Relativity interesting. According to Ogborn (2005), although students find Special Relativity very interesting when they first hear about the concept of time dilation and the mysterious formula of E=mc 2 , the mathematical difficulties that they experience when they meet the Lorentz transformations cause them to lose interest. In the present study, the mathematical difficulties stand out as one of the problems that the participants faced when learning about relativity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some studies point out the positive contributions of using the history of science to teach relativity (Arriassecq & Greca, 2012;Villani & Arruda, 1998). Ogborn (2005) suggests a sequence consisting of four steps for teachers to teach relativity. Among studies on special relativity, studies focusing on teaching by visualisation occupy an important place (Carr & Bossomaier, 2011;Henriksen et al,2014;Kortemeyer et al, 2013;Kraus, 2008;McGrath et al, 2010;Savage et al, 2007;Smith, 2011;Wegener et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ways of approaching the theory of relativity in physics teaching have been discussed by many groups of physicists and educators [8,[25][26][27][28][29][30][31][32][33][34]. In particular, the so-called mass-energy equivalence, represented by the famous formula E = mc 2 , opens a loophole for different modes of thought and, as a consequence, one finds divergent approaches in both textbooks and discourses by physicists.…”
Section: E = MC 2 and Implications For Teachingmentioning
confidence: 99%
“…According to this study, relativity is the second most interesting one among the other physics topics. According to Ogborn (2005), the students are quite enthusiastic when they start to learn relativity but they lose this enthusiasm of theirs when they face Lorentz's transformation and some complicated algebraic operations. According to the results of the study conducted by Angell (2004), teachers complain about the students' weak mathematical skills and the students do not regard mathematics as an important problem in physics lessons.…”
Section: Introductionmentioning
confidence: 99%